2012
DOI: 10.1002/da.21954
|View full text |Cite
|
Sign up to set email alerts
|

Killing in Combat May Be Independently Associated With Suicidal Ideation

Abstract: Background The United States military has lost more troops to suicide than to combat for the second year in a row and better understanding combat‐related risk factors for suicide is critical. We examined the association of killing and suicide among war veterans after accounting for PTSD, depression, and substance use disorders. Methods We utilized a cross‐sectional, retrospective, nationally representative sample of Vietnam veterans from the National Vietnam Veterans Readjustment Study (NVVRS). In order to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 35 publications
6
98
0
1
Order By: Relevance
“…Prior investigations in military samples have been conducted with small, treatment-seeking samples of active duty soldiers or veterans. Among these studies, some have found an independent association of PTSD and suicidality (Bush et al, 2011;Maguen et al, 2012b), and others have not (Bryan and Corso, 2011;Bryan et al, 2013;Griffith, 2012;Richardson et al, 2012). The results of this study are similar to those of large, epidemiological studies of civilian populations (Bernal et al, 2007;Bolton and Robinson, 2010;Nock et al, 2009Sareen et al, 2007) and underscore the importance of PTSD to future suicide risk in Army soldiers.…”
Section: Comorbidity Of Ptsd and Depressionsupporting
confidence: 84%
See 2 more Smart Citations
“…Prior investigations in military samples have been conducted with small, treatment-seeking samples of active duty soldiers or veterans. Among these studies, some have found an independent association of PTSD and suicidality (Bush et al, 2011;Maguen et al, 2012b), and others have not (Bryan and Corso, 2011;Bryan et al, 2013;Griffith, 2012;Richardson et al, 2012). The results of this study are similar to those of large, epidemiological studies of civilian populations (Bernal et al, 2007;Bolton and Robinson, 2010;Nock et al, 2009Sareen et al, 2007) and underscore the importance of PTSD to future suicide risk in Army soldiers.…”
Section: Comorbidity Of Ptsd and Depressionsupporting
confidence: 84%
“…In previous studies, similarly increased risks associated with PTSD have been reported (Calabrese et al, 2011;Guerra et al, 2011). Having PTSD was associated with three times the likelihood of reporting suicidality even after adjusting for depression, similar to prior research findings using military samples (Bush et al, 2011;Maguen et al, 2012b). Having both PTSD and depression were associated with a significantly greater risk of past-year suicidality than having either PTSD or depression alone.…”
Section: Comorbidity Of Ptsd and Depressionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recent research also shows a strong association between killing in combat and suicidal ideation for both Iraq and Vietnam era veterans (Maguen et al, 2011(Maguen et al, , 2012Rice & Sher, 2013).…”
mentioning
confidence: 99%
“…Moral injury is representative of the challenge of having to reconcile certain wartime experiences with individual interpretations of right and wrong and is purported to increase the risk of suicide in some Veteran populations (Kohlberg, 1973;Litz et al, 2009;Maguen et al, 2012). Interpretations of right and wrong may draw on individual experiences related to religion and/or spirituality.…”
Section: Veteran Spiritual Needsmentioning
confidence: 99%